Cataract Surgical Rate and Socioeconomics: A Global Study - Wang, Wei; Yan, William; Fotis, Kathy; Prasad, Noela M.; Lansingh, Van Charles; Taylor, Hugh R.; Finger, Robert P.; Facciolo, Damian; He, Mingguang (Investigative ophthalmology & visual science, 2016)
Cataract is the leading cause of blindness and cataract surgical rate (CSR) is used as a proxy indicator of access to cataract services in a country. The aim of this study was to explore the associations between the CSR and the economic development of countries in terms of gross domestic product per capital (GDP/P) and gross national income per capita (GNI/P). We systematically searched OVID (Medline and Embase), Pubmed, Embase.com, ISI Web of Science, and Cochrane Library databases, and retrieved additional data from unpublished reports. Cataract surgical rates and economic indicators (GDP/P, GNI/P) were collected for each country from 2005 to 2014. Complete data were used for the 50 largest countries according to World Health Organization (WHO) population estimates. Linear correlations between GDP/P and CSR were calculated. Cataract surgical rate data over two periods were used for analysis: 2005 to 2009 and 2010 to 2014 (CSR in 2009 or nearest year, CSR in 2014 or nearest year). Over the study period, CSR data were available for 152 countries across both time periods. Most of the CSR data were obtained from nongovernment organization (NGO) reports, including WHO reports. A good linear correlation between CSR and GDP/P was found overall, nearest to 2009 (β = 0.162, Linear: y = 0.162x + 282.242; R2 = 0.665, P < 0.001). Regression analysis of CSR nearest to 2014 produced similar findings, with significant correlations between CSR and GDP/P (Linear: y = 0.208x + 94.008; R2 = 0.785, P < 0.001). When using GNI/P as an economic indicator, similarly excellent lines of fit were obtained. After adjusting for time and country, CSR was significantly associated with GDP/P (Coefficient = 0.147, R2 = 0.759, P < 0.001), and GNI/P (Coefficient = 0.152, R2 = 0.757, P < 0.001). Most countries had an increase in CSRs over time, with the greatest increases observed for Iran and Argentina. Cataract surgical rate and economic indicators are closely associated, indicating the strong influence of resource availability on healthcare delivery. Considering this relationship, it is important to be innovative in delivery of low-cost services and invest strategically in capacity development to meet cataract surgical need in low-resource settings.